Monitoring Topographic Changes in a Periglacial High-mountain Face using High-resolution DTMs, Monte Rosa East Face, Italian Alps - Fischer, Luzia; Eisenbeiss, Henri; Kääb, Andreas; Huggel, Christian; Haeberli, Wilfried (Permafrost and Periglacial Processes, 2011)
ISSN:1045-6740 ISSN:1099-1530